Strategic Integration: Assessing the Influence of Academic Information Systems on Student Loyalty and Campus Facilities - Rolyana Ferinia Pintauli; Laverin Imelda Girsang (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2024)
Due to a lack of commitment during studying, students cannot complete their educational requirements on time. This study examines how an academic information system affects student loyalty to campus facilities as a mediating variable. Data collection for this study was done quantitatively using questionnaires and interviews—a non-probability sample of 73 people filled out the questionnaire. The data analysis method used in this study is PLS-SEM. First, the findings show that academic information systems do not significantly impact student loyalty. Second, campus facilities are significantly impacted by academic information systems. Third, school facilities have a significant impact on how loyal students are. Fourth, campus facilities significantly affect how academic information systems and student loyalty are related. This study's novelty is that to cultivate student loyalty, and it is crucial to adopt a simple, real-time multimedia technology to promote learning.